Sarcomatoid change in intrahepatic cholangiocarcinoma - Albrechtsen Wewer Nicolai; Zhang Da; Abdulkarim Bashar A.; Damjanov Ivan (Sanamed, 2013)
Sarcomatoid transformation is a rare but well documented change that may occur in intrahepatic cholangiocarcinomas. We report a tumor of this type to illustrate the difficulties in properly diagnosing cholangiocarcinoma when only the sarcomatous component is sampled by transcutaneous needle biopsy. The proper diagnosis of the tumor was suggested by finding the expression of cytokeratin 7 in the sarcomatous spindle cells. The surgically resected tumor comprised a spindle cell sarcomatous and an adenocarcinomatous component accounting for approximately 30% and 70% of the total tumor mass respectively